2016
DOI: 10.6018/analesps.32.3.230831
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ Trust in Social Consensus Varies by Context: Conventional vs. Moral Domains

Abstract: Título: La confianza de los niños en el consenso depende del contexto: convencional vs. moral. Resumen: Cuando una mayoría aprueba una exclusión social ¿los niños son fieles a sus opiniones personales o muestran deferencia hacia la mayoría? Teniendo en cuenta investigaciones previas sobre la preferencia de los niños por el testimonio de una mayoría de adultos frente al de un disidente cuando deben aprender palabras, en este trabajo se estudió esta preferencia por el consenso social en dos contextos: exclusión … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…According to this view, one would expect Spaniards to be in between these two cultures (U.S. and East Asian), in terms of rate of deference to consensus. However, contrary to this expectation, Guerrero et al (in press) found that Spanish preschoolers did not show any bias toward majority when endorsing new labels; instead, they were as likely to support the majority claim as the dissenter claim. Also, in the study by Enesco et al (in press), the Spanish preschoolers did not defer to the consensus but relied on their beliefs about counting procedures to accept or reject the majority’s assertions.…”
Section: Introductioncontrasting
confidence: 87%
See 4 more Smart Citations
“…According to this view, one would expect Spaniards to be in between these two cultures (U.S. and East Asian), in terms of rate of deference to consensus. However, contrary to this expectation, Guerrero et al (in press) found that Spanish preschoolers did not show any bias toward majority when endorsing new labels; instead, they were as likely to support the majority claim as the dissenter claim. Also, in the study by Enesco et al (in press), the Spanish preschoolers did not defer to the consensus but relied on their beliefs about counting procedures to accept or reject the majority’s assertions.…”
Section: Introductioncontrasting
confidence: 87%
“…Although we cannot directly compare these studies due to the large methodological differences, their general findings revealed that preschoolers were prone to oppose to a ‘morally wrong’ consensus, though the rate of resistance to consensus was higher among the Spanish preschoolers compared to the Americans. However, in the Guerrero et al (in press) study there was always a dissenter whose view coincided with that of the children. We do not know if children maintain the same position without the presence of an “allied” dissenter.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations